Influences of aluminum doping on the microstructures and electrical properties of tantalum nitride thin films before and after annealing. (March 2022) - Wang, Kao-Yuan; Chang, Ting-Chang; Chen, Wen-Chung; Zhang, Yong-Ci; Tseng, Yi-Ting; Yang, Chih-Cheng; Lin, Chun-Chu; Wu, Pei-Yu; Tan, Yung-Fang; Tsai, Tsung-Ming
Abstract: Ta–N–Al thin films were produced by reactive sputtering with two different TaAl alloys (Al 10 at.% and 20 at.%) for use as resistive materials for thin film chip resistors. Changing the N2 gas flow of the N2 /Ar plasma and the Al ratio in TaAl alloy resulted in different microstructures and electrical properties of the Ta–N–Al thin film. The resistivity of the thin film sputtered by TaAl (Al 20 at.%) alloy was 1.23 times that sputtered by Ta under 20% N2 /Ar. After deposition, rapid thermal processing was applied to anneal the thin films for 5 min at 600 °C, 650 °C, and 700 °C under N2 (99.995%) atmosphere, causing the Ta2 N and TaN crystalline phase formation. Al in Ta–N–Al was observed to hinder Ta2 N and TaN crystalline phase formation during annealing. It is crucial to dope Al ith Ta–N appropriately to obtain a near-zero temperature coefficient of resistance (TCR) after annealing. The TCR of Ta–N–Al thin film, sputtered by TaAl (Al 20 at.%) alloy, was substantially affected by the annealing temperature. However, the thin film sputtered by TaAl (Al 10 at.%) alloy under 16% N2 /Ar can achieve a TCR of −1.8 ppm/°C and 1.4 ppm/°C after annealing at 600 °C and 650 °C, respectively. Highlights: Ta-N-Al with adequate Al has a higher resistivity than Ta-N. Get near-zero TCR of Ta-N-Al by annealing within a specific temperature range. Al in Ta-N-Al hinders Ta2 N and TaN grain growth during annealing.